Advances in civil function structure and industrial architecture : proceedings of the 5th International Conference on Civil Function Structure and Industrial Architecture (CFSIA 2022), Harbin, China, 21-23 January 2022 /: proceedings of the 5th International Conference on Civil Function Structure and Industrial Architecture (CFSIA 2022), Harbin, China, 21-23 January 2022. (2022) - Unknown
No abstract available